Automation of the deployment of PHP applications - Bauer, Tomáš (2012)
This diploma thesis deals with the delivery of software products to end users and automation of related processes. After the initial introduction to the issue of deployment, as it is defined by one of the widely used software engineering methodology RUP (Rational Unified Process), the thesis devotes to practices as Continuous Integration, Continuous Delivery and Continuous Deployment which are directly oriented to the delivery of a software product based on automated processes. The second part depicts the design and the implementation of the solution for automation of the deployment of web applications in PHP within the specific developer company. The design part itself covers the analysis of the current state of the manual deploying process of business applications along with possible ways of automation its parts (updating the source code and database schema, application configuration, etc.), the definition of essential requirements for the solution and analysis of available tools which is the base for the selection of the most suitable tools for each component forming the resulting solution. The thesis also depicts interesting or nontrivial parts of implementation of each component, the practical case of usage of the system, the subsequent evaluation of the resulting solution along with estimated benefits and suggestions for the future expansion of its functionality.